Social Networks among Auction Bidders: The Role of Key Bidders and Structural Properties on Auction Prices - Dass, Mayukh (Institutional Knowledge at Singapore Management University, 2014)
Auctions have been studied extensively as an economic marketplace. The economist’s focus is on modeling final sales prices, but the processes that give rise to those outcomes are rarely studied in great detail. This research is intended to provide that complementary perspective. We show how the interactions between bidders in an auction unfold in a dynamic pattern of bids and counter-bids, and thereby over the duration of an auction, create a network structure. The auction network contributes significantly to models of price dynamics and the network predicts final sales prices better than economic (non-network) indicators alone. In addition, network analyses are useful in identifying the key bidders whose actions seem to exert disproportionate influence on other bidders and the final sales prices. Furthermore, the key bidders may be identified very early in an auction process, which has practical implications for the auction house managers and for other bidders.